2013
DOI: 10.1111/ajt.12218
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Resolving Polyomavirus-Associated Nephropathy

Abstract: These authors contributed equally.Control of polyomavirus BK (BKV) is achieved by reducing immunosuppression allowing an effective BKV-specific T-cell response. The morphology of resolving BKV-associated nephropathy (PyVAN) has not been systematically investigated. Ninety-nine surveillance biopsies of 35 patients with BKV viremia treated exclusively by immunosuppression reduction were scored according to Banff criteria and grouped relative to BKV viremia as pre-, increasing, decreasing and post-BKV viremia. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
108
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 39 publications
(61 reference statements)
13
108
0
2
Order By: Relevance
“…9 However, recent studies showed that, in some of the patients with BKPyVAN, HLA-DR expression is also present. 5,10 Our study is in line with these recent publications. It is known that HLA-DR expression can stimulate an allogeneic lymphocytic reaction and enhance T cell-mediated lysis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…9 However, recent studies showed that, in some of the patients with BKPyVAN, HLA-DR expression is also present. 5,10 Our study is in line with these recent publications. It is known that HLA-DR expression can stimulate an allogeneic lymphocytic reaction and enhance T cell-mediated lysis.…”
Section: Discussionsupporting
confidence: 92%
“…31 The biopsies of the BKPyVAN cohort were also scored according to the BKPyVAN grading system as proposed by Hirsch et al 18 HLA-DR expression on epithelial cells was not considered a sign of rejection, because it was also observed in patients with BKPyVAN. 10,11 The percentages of missing staining because of unavailability of material per diagnosis are shown in Supplemental Table 1.…”
Section: Histopathologic Examination and Immunophenotypical Quantificmentioning
confidence: 99%
See 1 more Smart Citation
“…In kidney transplantation (KT), high‐level BKPyV viruria and viremia have been identified as markers of progression to PyVAN 25, thus current management strategies recommend screening KTRs for viremia followed by reducing immunosuppression 26, 27, 28. In prospective observational studies, this preemptive intervention has been successful, as shown by clearance of viremia and PyVAN in 80–100% of cases, with a low risk of subsequent acute rejection in 0–14% of patients 29, 30, 31, 32, 33. BKPyV viremia clearance has been paralleled by increasing BKPyV‐specific T cell responses in peripheral blood 30, 34, 35, 36.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of rebound inflammation after a successfully treated polyomavirus has recently been proposed, but additional data are needed (Table 4). 117,126,127 Sampling must also be factored in; tubular infection is patchy, and a core biopsy may miss diagnostic tubules, especially if the biopsy is solely from the renal cortex. 126 These observations emphasize the importance of correlating biopsy histology, IHC, trends in viral serology, and renal function in assessing patients with polyomavirus.…”
Section: Viral Infectionsmentioning
confidence: 99%